Answer:
Step-by-step explanation:
![\begin{matrix}1\\1&1\\1&2&1\\1&3&3&1\\1&4&6&4&1\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bmatrix%7D1%5C%5C1%261%5C%5C1%262%261%5C%5C1%263%263%261%5C%5C1%264%266%264%261%5Cend%7Bbmatrix%7D)
The rows add up to
![1,2,4,8,16](https://tex.z-dn.net/?f=1%2C2%2C4%2C8%2C16)
, respectively. (Notice they're all powers of 2)
The sum of the numbers in row
![n](https://tex.z-dn.net/?f=n)
is
![2^{n-1}](https://tex.z-dn.net/?f=2%5E%7Bn-1%7D)
.
The last problem can be solved with the binomial theorem, but I'll assume you don't take that for granted. You can prove this claim by induction. When
![n=1](https://tex.z-dn.net/?f=n%3D1)
,
![(1+x)^1=1+x=\dbinom10+\dbinom11x](https://tex.z-dn.net/?f=%281%2Bx%29%5E1%3D1%2Bx%3D%5Cdbinom10%2B%5Cdbinom11x)
so the base case holds. Assume the claim holds for
![n=k](https://tex.z-dn.net/?f=n%3Dk)
, so that
![(1+x)^k=\dbinom k0+\dbinom k1x+\cdots+\dbinom k{k-1}x^{k-1}+\dbinom kkx^k](https://tex.z-dn.net/?f=%281%2Bx%29%5Ek%3D%5Cdbinom%20k0%2B%5Cdbinom%20k1x%2B%5Ccdots%2B%5Cdbinom%20k%7Bk-1%7Dx%5E%7Bk-1%7D%2B%5Cdbinom%20kkx%5Ek)
Use this to show that it holds for
![n=k+1](https://tex.z-dn.net/?f=n%3Dk%2B1)
.
![(1+x)^{k+1}=(1+x)(1+x)^k](https://tex.z-dn.net/?f=%281%2Bx%29%5E%7Bk%2B1%7D%3D%281%2Bx%29%281%2Bx%29%5Ek)
![(1+x)^{k+1}=(1+x)\left(\dbinom k0+\dbinom k1x+\cdots+\dbinom k{k-1}x^{k-1}+\dbinom kkx^k\right)](https://tex.z-dn.net/?f=%281%2Bx%29%5E%7Bk%2B1%7D%3D%281%2Bx%29%5Cleft%28%5Cdbinom%20k0%2B%5Cdbinom%20k1x%2B%5Ccdots%2B%5Cdbinom%20k%7Bk-1%7Dx%5E%7Bk-1%7D%2B%5Cdbinom%20kkx%5Ek%5Cright%29)
![(1+x)^{k+1}=1+\left(\dbinom k0+\dbinom k1\right)x+\left(\dbinom k1+\dbinom k2\right)x^2+\cdots+\left(\dbinom k{k-2}+\dbinom k{k-1}\right)x^{k-1}+\left(\dbinom k{k-1}+\dbinom kk\right)x^k+x^{k+1}](https://tex.z-dn.net/?f=%281%2Bx%29%5E%7Bk%2B1%7D%3D1%2B%5Cleft%28%5Cdbinom%20k0%2B%5Cdbinom%20k1%5Cright%29x%2B%5Cleft%28%5Cdbinom%20k1%2B%5Cdbinom%20k2%5Cright%29x%5E2%2B%5Ccdots%2B%5Cleft%28%5Cdbinom%20k%7Bk-2%7D%2B%5Cdbinom%20k%7Bk-1%7D%5Cright%29x%5E%7Bk-1%7D%2B%5Cleft%28%5Cdbinom%20k%7Bk-1%7D%2B%5Cdbinom%20kk%5Cright%29x%5Ek%2Bx%5E%7Bk%2B1%7D)
Notice that
![\dbinom k\ell+\dbinom k{\ell+1}=\dfrac{k!}{\ell!(k-\ell)!}+\dfrac{k!}{(\ell+1)!(k-\ell-1)!}](https://tex.z-dn.net/?f=%5Cdbinom%20k%5Cell%2B%5Cdbinom%20k%7B%5Cell%2B1%7D%3D%5Cdfrac%7Bk%21%7D%7B%5Cell%21%28k-%5Cell%29%21%7D%2B%5Cdfrac%7Bk%21%7D%7B%28%5Cell%2B1%29%21%28k-%5Cell-1%29%21%7D)
![\dbinom k\ell+\dbinom k{\ell+1}=\dfrac{k!(\ell+1)}{(\ell+1)!(k-\ell)!}+\dfrac{k!(k-\ell)}{(\ell+1)!(k-\ell)!}](https://tex.z-dn.net/?f=%5Cdbinom%20k%5Cell%2B%5Cdbinom%20k%7B%5Cell%2B1%7D%3D%5Cdfrac%7Bk%21%28%5Cell%2B1%29%7D%7B%28%5Cell%2B1%29%21%28k-%5Cell%29%21%7D%2B%5Cdfrac%7Bk%21%28k-%5Cell%29%7D%7B%28%5Cell%2B1%29%21%28k-%5Cell%29%21%7D)
![\dbinom k\ell+\dbinom k{\ell+1}=\dfrac{k!(\ell+1)+k!(k-\ell)}{(\ell+1)!(k-\ell)!}](https://tex.z-dn.net/?f=%5Cdbinom%20k%5Cell%2B%5Cdbinom%20k%7B%5Cell%2B1%7D%3D%5Cdfrac%7Bk%21%28%5Cell%2B1%29%2Bk%21%28k-%5Cell%29%7D%7B%28%5Cell%2B1%29%21%28k-%5Cell%29%21%7D)
![\dbinom k\ell+\dbinom k{\ell+1}=\dfrac{k!(k+1)}{(\ell+1)!(k-\ell)!}](https://tex.z-dn.net/?f=%5Cdbinom%20k%5Cell%2B%5Cdbinom%20k%7B%5Cell%2B1%7D%3D%5Cdfrac%7Bk%21%28k%2B1%29%7D%7B%28%5Cell%2B1%29%21%28k-%5Cell%29%21%7D)
![\dbinom k\ell+\dbinom k{\ell+1}=\dfrac{(k+1)!}{(\ell+1)!((k+1)-(\ell+1))!}](https://tex.z-dn.net/?f=%5Cdbinom%20k%5Cell%2B%5Cdbinom%20k%7B%5Cell%2B1%7D%3D%5Cdfrac%7B%28k%2B1%29%21%7D%7B%28%5Cell%2B1%29%21%28%28k%2B1%29-%28%5Cell%2B1%29%29%21%7D)
![\dbinom k\ell+\dbinom k{\ell+1}=\dbinom{k+1}{\ell+1}](https://tex.z-dn.net/?f=%5Cdbinom%20k%5Cell%2B%5Cdbinom%20k%7B%5Cell%2B1%7D%3D%5Cdbinom%7Bk%2B1%7D%7B%5Cell%2B1%7D)
So you can write the expansion for
![n=k+1](https://tex.z-dn.net/?f=n%3Dk%2B1)
as
![(1+x)^{k+1}=1+\dbinom{k+1}1x+\dbinom{k+1}2x^2+\cdots+\dbinom{k+1}{k-1}x^{k-1}+\dbinom{k+1}kx^k+x^{k+1}](https://tex.z-dn.net/?f=%281%2Bx%29%5E%7Bk%2B1%7D%3D1%2B%5Cdbinom%7Bk%2B1%7D1x%2B%5Cdbinom%7Bk%2B1%7D2x%5E2%2B%5Ccdots%2B%5Cdbinom%7Bk%2B1%7D%7Bk-1%7Dx%5E%7Bk-1%7D%2B%5Cdbinom%7Bk%2B1%7Dkx%5Ek%2Bx%5E%7Bk%2B1%7D)
and since
![\dbinom{k+1}0=\dbinom{k+1}{k+1}=1](https://tex.z-dn.net/?f=%5Cdbinom%7Bk%2B1%7D0%3D%5Cdbinom%7Bk%2B1%7D%7Bk%2B1%7D%3D1)
, you have
![(1+x)^{k+1}=\dbinom{k+1}0+\dbinom{k+1}1x+\cdots+\dbinom{k+1}kx^k+\dbinom{k+1}{k+1}x^{k+1}](https://tex.z-dn.net/?f=%281%2Bx%29%5E%7Bk%2B1%7D%3D%5Cdbinom%7Bk%2B1%7D0%2B%5Cdbinom%7Bk%2B1%7D1x%2B%5Ccdots%2B%5Cdbinom%7Bk%2B1%7Dkx%5Ek%2B%5Cdbinom%7Bk%2B1%7D%7Bk%2B1%7Dx%5E%7Bk%2B1%7D)
and so the claim holds for
![n=k+1](https://tex.z-dn.net/?f=n%3Dk%2B1)
, thus proving the claim overall that
![(1+x)^n=\dbinom n0+\dbinom n1x+\cdots+\dbinom n{n-1}x^{n-1}+\dbinom nnx^n](https://tex.z-dn.net/?f=%281%2Bx%29%5En%3D%5Cdbinom%20n0%2B%5Cdbinom%20n1x%2B%5Ccdots%2B%5Cdbinom%20n%7Bn-1%7Dx%5E%7Bn-1%7D%2B%5Cdbinom%20nnx%5En)
Setting
![x=1](https://tex.z-dn.net/?f=x%3D1)
gives
![(1+1)^n=\dbinom n0+\dbinom n1+\cdots+\dbinom n{n-1}+\dbinom nn=2^n](https://tex.z-dn.net/?f=%281%2B1%29%5En%3D%5Cdbinom%20n0%2B%5Cdbinom%20n1%2B%5Ccdots%2B%5Cdbinom%20n%7Bn-1%7D%2B%5Cdbinom%20nn%3D2%5En)
which agrees with the result obtained for part (c).
Answer:
0 boxes minimum
Step-by-step explanation:
The mass of the truck and paper must satisfy ...
22.5b + 2948.35 ≤ 4700 . . . . total truck mass cannot exceed bridge limits
22.5b ≤ 1751.65
b ≤ 77.85
The driver can take a minimum of 0 boxes and a maximum of 77 boxes of paper over the bridge.
_____
The question asks for the <em>minimum</em>. We usually expect such a question to ask for the <em>maximum</em>.
The zero normally gives it away for example: 10,20,30,40,50